Macroprudential financial market regulation: aims, implementation, and implications for developing and emerging economies - Birgit Schmitz (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
The global financial crisis has shown that financial market regulation focused on the liquidity and solvency position of individual financial intermediaries does not suffice to mitigate the overall risks to financial stability. Furthermore, the real economic costs of financial instability are considerably higher than expected. A core element of the international policy response to the crisis has been to strengthen the macroprudential orientation of financial market regulation. Macroprudential policy and regulation stand for enhanced regulatory focus on systemic risks in the financial system and their repercussions for the macroeconomy. Thus far, the debate on macroprudential regulation has mainly focused on the needs of developed economies and examined regulatory proposals against the background of advanced economies. However, empirical evidence shows that developing and emerging economies have suffered stronger and more costly economic cycles and disruptive financial crises than advanced economies – with less effective fiscal and monetary policy tools to mitigate and resolve them. In preparation for future shocks, policy makers in developing countries must urgently develop macroprudential policy frameworks to foster financial and macroeconomic stability. This paper presents the most important aspects of macroprudential policy making for developing and emerging economies. It explains the concepts of macroprudential regulation and introduces how macroprudential policy is currently being implemented. It then identifies the major sources of systemic risk and discusses the specific challenges to developing macroprudential policy frameworks for developing and emerging economies, and offers recommendations with regard to macroprudential policy choices for developing and emerging economies.
Keywords: 330